Internalizing negative environmental impacts from wind power production: Coasian bargaining, offsetting schemes and environmental taxes - Mads Greaker; Cathrine Hagem; Andreas Skulstad (Statistics Norway, Research Department, 2022)
On the one hand, wind power production is necessary for decarbonizing the electricity sector. On the other hand, we risk replacing one environmental problem with other environmental problems, that is, stopping climate change in exchange with increased loss of pristine land and biodiversity. The present paper provides a novel contribution to the literature on how to regulate the development of wind power plants (WPPs). Current regulation is largely based on a concession system, where both environmental taxes and offset schemes are left unexplored. We develop a theoretical model of WPP development with offsets and environmental taxes. We show that if additional loss of pristine nature and biodiversity is acceptable at some monetary price, establishing an offset market for WPP development and combining it with an environmental tax will be socially desirable. In fact, this solution is preferable to both only having an environmental tax or only having a compulsory offset market. However, if no more loss of pristine land and biodiversity can be tolerated, compulsory and complete offsetting should be the norm. We look at two restoration projects in Norway and evaluate to what extent they could have been used as offsets for a recent WPP development in Norway. We conclude that they can, but an offset scheme demands good measurement methods and regulations to ensure equivalence in the values of ecosystem services lost and gained.
Keywords: D62; Q24; Q26; Q42; Q48; Q51; Q56; Q57; Q58; 330; Wind power; Offsetting schemes; Environmental taxes; Resource Equivalency Analysis; Habitat Equivalency Analysis